IN VITRO IRREVERSIBLE BINDING AND DEGRADATION OF (R)- AND (S)-KETOPROFEN GLUCURONIDES TO PLASMA PROTEINS - PETER J. HAYBALL; KELLIE L. TUCK (Malaysian Journal of Pharmaceutical Sciences, 2007)
This study describes the in vitro degradation studies of the diastereomeric ketoprofen glucuronides, under physiological conditions (pH 7.4, 37°C, (R)-ketoprofen glucuronide t½ = 30 min, (S)-ketoprofen glucuronide t½ = 70 min) and the irreversible binding of diastereomeric ketoprofen glucuronides (15 μg/ml) to human serum albumin (HSA) (289 μM) and human plasma under physiological conditions (pH 7.4, 37ºC). The (R)-ketoprofen glucuronide irreversibly bound to a greater extent in both human plasma and human serum albumin. This is the reverse to that found in previous studies. These findings further support the hypothesis that faster degradation of 1-O-acyl glucuronide (in this case the (R)-diastereomer) is associated with a greater extent of irreversible binding.